2017
DOI: 10.1101/144386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systems biology analysis using a genome-scale metabolic model shows that phosphine triggers global metabolic suppression in a resistant strain ofC. elegans

Abstract: (148 words < 350 words)Background: Pest insects are increasingly resistant to phosphine gas, which is used globally to protect grain reserves. The enzyme dihydrolipoamide dehydrogenase (DLD) is a phosphine resistance factor and participates in four key steps of core metabolism, making it a potential central metabolic regulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…ElegCyc used PathwayTools (Karp et al, 2016 ), while iCEL1273 is based on a new workflow developed by the authors. Finally, in 2017 CeCon, also based on PathwayTools, was published by Ma et al ( 2017 ). Table 1 summarizes key metrics of each model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ElegCyc used PathwayTools (Karp et al, 2016 ), while iCEL1273 is based on a new workflow developed by the authors. Finally, in 2017 CeCon, also based on PathwayTools, was published by Ma et al ( 2017 ). Table 1 summarizes key metrics of each model.…”
Section: Resultsmentioning
confidence: 99%
“…To begin merging, ElegCyc was obtained in SBML format from the Supplementary Information of Gebauer et al ( 2016 ), and an SBML format of CeCon (Ma et al, 2017 ) was exported from Pathway Tools. The two models were then translated into the MetaNetX format (Moretti et al, 2016 ), and imported into MATLAB for merging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several GSMs for the biomedical model organisms Caenorhabditis elegans have been described and recently merged into the WormJam consensus model [7][8][9][10]. This model aims to represent accurately the current knowledge on C. elegans metabolism to facilitate both modeling and metabolomics data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…During the workshop, ongoing efforts were identified that are merging and reconciling the two published models mentioned above, as well as other unpublished models developed in different labs (http://cai-gsmodel.cai.uq.edu.au), 8 into consensus reconstructions. The models are partially overlapping and far from complete; many metabolites that can be identified and quantified in C. elegans are not represented.…”
Section: Introductionmentioning
confidence: 99%